2010
DOI: 10.1111/j.1600-0781.2010.00492.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of human papilloma virus in untreated and ultraviolet-treated psoriatic patients

Abstract: UV treatment may be an underlying factor predisposing patients with psoriasis to infectivity by HPV together with other factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Salem and colleagues demonstrated recovery of more HPV in psoriatic plaques treated with UVB and psoralen plus UVA (PUVA) than in nonirradiated psoriatic plaques and normal controls. 45 That same study found that there was an even greater recovery in PUVA-treated patients with psoriasis than in those treated with narrowband UVB (NB-UVB), suggesting that the UV wavelength and degree of damage is important in HPV infection. Furthermore, when the authors examined UV-treated patients with vitiligo, they found that HPV recovery in lesional skin in these patients was similar to that in the psoriasis-PUVA group but significantly higher than in the psoriasis-NB-UVB group.…”
Section: Ultraviolet Light and Hpvmentioning
confidence: 96%
See 2 more Smart Citations
“…Salem and colleagues demonstrated recovery of more HPV in psoriatic plaques treated with UVB and psoralen plus UVA (PUVA) than in nonirradiated psoriatic plaques and normal controls. 45 That same study found that there was an even greater recovery in PUVA-treated patients with psoriasis than in those treated with narrowband UVB (NB-UVB), suggesting that the UV wavelength and degree of damage is important in HPV infection. Furthermore, when the authors examined UV-treated patients with vitiligo, they found that HPV recovery in lesional skin in these patients was similar to that in the psoriasis-PUVA group but significantly higher than in the psoriasis-NB-UVB group.…”
Section: Ultraviolet Light and Hpvmentioning
confidence: 96%
“…The destructive effects of UV light may also play a role in HPV infection. Salem and colleagues demonstrated recovery of more HPV in psoriatic plaques treated with UVB and psoralen plus UVA (PUVA) than in nonirradiated psoriatic plaques and normal controls . That same study found that there was an even greater recovery in PUVA‐treated patients with psoriasis than in those treated with narrowband UVB (NB‐UVB), suggesting that the UV wavelength and degree of damage is important in HPV infection.…”
Section: Ultraviolet Light and Hpvmentioning
confidence: 98%
See 1 more Smart Citation
“…This difference is likely to reflect the facts that non-scar SCC is more common in countries with predominantly light-skinned populations and that UV-induced SCC is relatively less common in countries with dark-skinned individuals. 33 Immunocompromised individuals have a high risk for acquiring HPV and subsequent malignant transforma-tion because the adaptive immune system (functional T cell response) is integral to fighting HPV infection. 4).…”
Section: Pathogenesismentioning
confidence: 99%
“…The hypothesis was to verify whether there was a relation between the clinical evolution of the disease and the presence of HPV as an aggravating factor (9,15).…”
Section: Discussionmentioning
confidence: 99%